Extraction of peroxidase from bitter gourd (Momordica charantia) by three phase partitioning with dimethyl carbonate (DMC) as organic phase. (October 2017) - Panadare, Dhanashree C.; Rathod, Virendra K.
Graphical abstract: Highlights: Dimethyl Carbonate was explored as organic phase for the first time in three phase partitioning. Parameters; salts, solvents, ratio of aqueous to organic, time, pH and temperature were optimised. Peroxidase from bitter gourd waste with 4.89 fold purity and 177% recovery was obtained by TPP. Bitter gourd peroxidase was successfully employed to degrade methylene blue dye. Abstract: Three phase partitioning (TPP) is most renowned technique used for extraction and purification of natural products. In previous studies of TPP, t -butanol is mainly used as an organic phase. This is the first report that explores ability of dimethyl carbonate (DMC) in the field of TPP as an alternate solvent for t -butanol. In the present study TPP process with t -butanol and DMC as organic phase along with different salts was applied to waste bitter gourd powder to obtained peroxidase enzyme. DMC was found to be compatible with most of salts such as ammonium sulphate and sodium citrate and explored as more efficient solvent than t -butanol. This TPP system provides 4.84 fold purity of peroxidase enzyme at optimum source concentration of 0.15 g/mL, with a system comprising DMC as organic phase, sodium citrate (20%) as salt, agitation speed 120 rpm, pH 7, temperature 30 °C and extraction time of 3 h. Present study has aimed for extraction and separation of peroxidase from bitter gourd waste with TPP technique and ensures the scope of carbonated solvents in extraction and purification of proteins.